The Effect of Sustainable Livelihoods on the COVID-19 Disaster Recovery in Agrotourism - Verlina Intan Wulandari; Qomariyatus Sholihah; Rita Parmawati (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2022)
Kebun Belimbing Ngringinrejo is the leading agrotourism in Bojonegoro Regency. COVID-19 pandemic has decreased a numeral of tourist visits which caused agrotourism income to decline, business actors, to lose their jobs, and the livelihoods of starfruit farmers to be threatened. After the COVID-19 vaccination, the re-opening of agrotourism began with the application of health protocols. Agrotourism must carry out a recovery process to return to normality. The study aims to determine the condition of sustainable livelihoods for star fruit farmers and business actors and the effect of livelihood assets on disaster recovery. This research was conducted so that agrotourism can recover immediately by optimizing high assets and improving low assets. This study used the descriptive statistic and analysis of SEM-PLS. The outcome indicated that the condition of sustainable livelihoods for starfruit farmers and business actors has a high natural, social, and physical assets. At the same time, low assets are human and financial assets. Four sustainable livelihood assets are human, natural, social, and physical, significantly influencing disaster recovery. In contrast, financial assets have no significant impact on disaster recovery. The most significant indicators for the disaster recovery process in agrotourism are developing digital solutions, and the lowest indicator is designing risk communication.